SIMILARITY AND DIFFERENCES ASPECTS OF GRADUONIMIC SERIES FORMED BY SEMANTIC CATEGORIES OF VERBS IN UZBEK AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2023)
This article is presented as an example of research on the study of the graduonymy of verbs in the Uzbek and English languages, and the similar and different aspects of the graduonymy series formed according to the semantic categories of the verbs in the languages ​​being compared. cited. Also, in the article, the semantic categories of verbs of action, verbs of speech, verbs of state, mental verbs, action verbs of result in Uzbek and verbs of action, mental verbs, verbs of reason in English Verbs were separated into semantic groups such as verbs, verbs of the state of occurrence, aspect verbs, and the verbs were analyzed from the explanatory dictionaries, and graduonymic rows were created with the participation of their synonyms and opposite meanings. The constructed graduonymic series are interspersed with their equivalents in both languages. As a result of the cross-sectional analysis, it was found that there are similar, different or completely unique gradation lines in the Uzbek and English languages. As a result, when comparing the graduonymic rows formed from verbs in the Uzbek and English languages, it was found that the number of members in the English language lines is relatively larger. In addition, it was found that in Uzbek language there is a graduonymic rows with the presence of gendered words, such a graduonymicseries does not exist in English.